Does being accompanied make a difference in communication during breast cancer consultations? Results from a multi-centered randomized controlled trial. Issue 2 (4th March 2021) - Buizza, Chiara; Cela, Herald; Ferrari, Clarissa; Goss, Claudia; Bottacini, Alessandro; Mazzi, Maria Angela; Del Piccolo, Lidia; Ghilardi, Alberto
Abstract: Objectives: This study is based on a multi-centered RCT conducted on breast cancer patients during their first consultation with an oncologist. The main aim was to evaluate whether the introduction of a communication tool (i.e., the Question Prompt Sheet or Question Listing), with or without a companion, impacted the number of questions asked by patients during the consultation, and subsequent psychological and relational outcomes. Methods: The sample consisted of 324 breast cancer patients who were randomly placed into one of the two intervention groups: Question Prompt Sheet or Question Listing. Before and after the consultation, patients completed a set of standardized instruments: Satisfaction with decisions made during the consultation (SWD), Shared Decision Making Questionnaire (SDMQ-9), Patient Enablement Instrument (PEI), Patient Health Questionnaire Depression scale (PHQ-9), General Health Questionnaire (GHQ-12), Results: The results indicate that the number of questions asked during the consultation was higher when a Question Listing was provided and when the patient was unaccompanied. Unaccompanied patients asked more questions in both groups and had significantly lower scores than accompanied on the GHQ-12 and on the PHQ-9, indicating lower clinical symptomatology. Conclusions: Results are in contrast with previous literature, indicating that being unaccompanied help patients to interact more with the oncologist. Further studies are needed to evaluate how the presence or not of a companion really impacts breast cancer patients during their first consultation with an oncologist. Trial registration: ClinicalTrials.gov NCT01510964